Access to a Labile Monomeric Magnesium Radical by Ball-Milling - Jedrzkiewicz, Dawid; Mai, Jonathan; Langer, Jens; Mathe, Zachary; Patel, Neha; DeBeer, Serena; Harder, Sjoerd (Angewandte Chemie International Edition, 2022)
In order to isolate a monometallic Mg radical, the precursor (Am)MgI⋅(CAAC) (1) was prepared (Am=tBuC(N-DIPP)2, DIPP=2,6-diisopropylphenyl, CAAC=cyclic (alkyl)(amino)carbene). Reduction of a solution of 1 in toluene with the reducing agent K/KI led to formation of a deep purple complex that rapidly decomposed. Ball-milling of 1 with K/KI gave the low-valent MgI complex (Am)Mg⋅(CAAC) (2) which after rapid extraction with pentane and crystallization was isolated in 15 % yield. Although a benzene solution of 2 decomposes rapidly to give Mg(Am)2 (3) and unidentified products, the radical is stable in the solid state. Its crystal structure shows planar trigonal coordination at Mg. The extremely short Mg−C distance of 2.056(2) Å indicates strong Mg−CAAC bonding. Calculations and EPR measurements show that most of the spin density is in a π* orbital located at the C−N bond in CAAC, leading to significant C−N bond elongation. This is supported by calculated NPA charges in 2: Mg +1.73, CAAC −0.82. Similar metal-to-CAAC charge transfer was calculated for M0(CAAC)2 and [MI(CAAC)2+] (M=Be, Mg, Ca) complexes in which the metal charges range from +1.50 to +1.70. Although the spin density of the radical is mainly located at the CAAC ligand, complex 2 reacts as a low-valent MgI complex: reaction with a I2 solution in toluene gave (Am)MgI⋅(CAAC) (1) as the major product.
CRIS-Team Scopus Importer:2022-02-25
Keywords: DFT Calculations; EPRSpectroscopy; Low-Valent Complexes; Magnesium; Radicals